Implementasi Lean Manufacturing pada Industri Makanan: Kajian Literatur - Martis, Andi; Pirmansyah, Rd Iman; Purba, Humiras Hardi (Universitas Mercu Buana, 2023)
Companies that are able to survive in fierce competition in the market are not companies that have large capital, but companies that are able to respond quickly to market demand. For this reason, companies need to improve all lines to achieve effective and efficient productivity levels. The implementation of lean manufacturing can be carried out in production companies so that they are able to provide quality products according to market demand and have low costs without having to reduce the added value of their products. The purpose of this research is to find steps to reduce various kinds of waste in the production line by using lean manufacturing principles in the food industry. A literature review was carried out using the following criteria: lean manufacturing, food production, tools used in lean manufacturing, and the waste that occurs. The results obtained from the literature review are by implementing lean manufacturing on production lines that are able to reduce costs, improve long process flows, but must be accompanied by the company's readiness to support financially and other things.